2008
DOI: 10.1186/1471-2377-8-38
|View full text |Cite
|
Sign up to set email alerts
|

A novel needle for subcutaneous injection of interferon beta-1a: effect on pain in volunteers and satisfaction in patients with multiple sclerosis

Abstract: BackgroundTo reduce injection pain and improve satisfaction, a thinner (29-gauge [29G]), sharper (5-bevel) needle than the 27G/3-bevel needle used previously to inject interferon (IFN) beta-1a, 44 or 22 mcg subcutaneously (sc) three times weekly (tiw), was developed for use in multiple sclerosis (MS).MethodsTwo clinical trials in healthy volunteers and five surveys of patients with MS were conducted to assess whether the 29G/5-bevel needle with a Thermo Plastic Elastomer (TPE) needle shield (a sleeve that hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 5 publications
2
50
0
Order By: Relevance
“…40,41 Educating the patient on appropriate injection techniques, the availability of new injection devices, the use of escalating dosages, and concomitant administration of nonsteroidal anti-inflammatory drugs (NSAIDs) can minimize these adverse events and thus increase adherence. 32,[42][43][44][45][46][47] Physician-documented disease progression was another factor in nonadherence in our study, with 17.7% of nonadherent patients discontinuing their DMTs upon being told that the disease had entered a progressive phase and the likelihood of ongoing beneficial effects was low. This rate is lower than other published data, but the number of SPMS patients included in our analysis was small.…”
Section: Figure 2 Reasons For Discontinuation Of Various Disease-modmentioning
confidence: 91%
“…40,41 Educating the patient on appropriate injection techniques, the availability of new injection devices, the use of escalating dosages, and concomitant administration of nonsteroidal anti-inflammatory drugs (NSAIDs) can minimize these adverse events and thus increase adherence. 32,[42][43][44][45][46][47] Physician-documented disease progression was another factor in nonadherence in our study, with 17.7% of nonadherent patients discontinuing their DMTs upon being told that the disease had entered a progressive phase and the likelihood of ongoing beneficial effects was low. This rate is lower than other published data, but the number of SPMS patients included in our analysis was small.…”
Section: Figure 2 Reasons For Discontinuation Of Various Disease-modmentioning
confidence: 91%
“…More recently, a similar study examining response in 30-gauge versus 29-gauge versus 27-gauge syringe needles also showed that penetration force correlated with needle diameter. 43 Both patients and HCPs have reported less pain and greater preference for thinner needles in comparisons of 33-gauge tips versus 31-gauge needles (unblinded), 44 29-gauge versus 27-gauge in blinded multiple sclerosis patients using prefilled syringes, 45 29-gauge versus 27-gauge in blinded multiple sclerosis patients, 46 32-gauge versus 30-gauge pen needles (unblinded), 47 32-gauge versus 31-gauge pen needles, 38 and in comparison of 31-gauge needles, normal to thin wall. 48 Finally, Japanese patients found less pain and bruising using a 33-gauge needle in a crossover study with a 31-gauge comparator needle.…”
Section: Aronsonmentioning
confidence: 99%
“…Asakura et al 44 compared two different tip gauges and found less pain with a 29-gauge microtapered needle that slimmed to a 33-gauge tip. In two French trials, covering 241 patients, less pain was found with a five-bevel tip 45 that happened to be on a narrower 29-gauge needle. The comparison by Mayer et al 43 of piercing forces of three needle gauges also included comparisons of five-bevel and three-bevel tips, but found that gauge was the primary determinant of cutting and piercing force.…”
Section: Aronsonmentioning
confidence: 99%
“…9 Differences between insertion forces of these 3-and 5-bevel needle tips originally observed in the laboratory were also demonstrated in healthy volunteers and in patients' subjective experience using the needles to inject interferon for multiple sclerosis. 10 This study was undertaken to demonstrate the acceptability of the 5-bevel needle ( Figure 1B) in patients injecting insulin and to compare perceived pain and preference between 3-and 5-bevel needles.…”
Section: Introductionmentioning
confidence: 99%